École Méthodique in Historiography: Concept, Theoretical Basis and Connections with Lithuania - Gieda, Aurelijus (Lietuvos istorijos studijos, 2016)
In general, different historiographical schools often remain on the fringes of academic interest when conducting historiographical research in Lithuania. The aim of this article is to characterize the historiography school in France which dominated the academic history science in the Third French Republic (1870–1940) through the opportunities offered by the ideas of history studies and historiography according to the criteria selected. The article tries to reveal the École Méthodique concept in historiography and to show the school’s theoretical beliefs and understanding of historical methodology. The article analyses the historiographical origins of the school, the so-called methodical turn in historiography, and highlights the canonical texts which created the school and constituted its nature. For more conceptual look the article considers the issue how historiographical traditions of the Third Republic are analysed in today’s historiography history and deals with problematic issues (e.g., whether the term positivism is suitable for the analysis of historiography evolution). The Lithuanian relevance of the article is based on the identification of relationships and parallels, and the search of French historiographical school activities in emerging Lithuanian historiographical tradition. The article aims to answer the question: what relationships and parallels can be seen when looking at the École Méthodique in France in view of emerging Lithuanian historiography in the first half of the 20th century? The conclusion states that some of the most authoritative pre-war Lithuanian historians expressed their sympathy to the French history method version. The article provides a more profound view on the question of French and Lithuanian historiography relationship.